Effect of skipping on body mass index, waist to hip ratio and muscle strength in overweight adolescent girls - Dhiya Fadhila Rahmah; Hadi Riyadi; Hardinsyah Hardinsyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Overweight problems in adolescents tend to increase, with obese nutritional status prevalence for Indonesian teenagers in group aged–13-15 and 16-18 years respectively 11,2% and 9,5%. This study aimed to analyze the effect of skip training on body mass index for age z-score (BAZ), waist-to-hip ratio (WHR), and muscle strength in overweight adolescent girls. The method of this research was a quasi-experimental design using a subject study of 28 female students, who were divided into two groups: those age between 15-18 years old. This study was conducted at Senior High School 1 West Sumatra and Batipuh from October to December 2023. The skipping group received 4-8 minutes of exercise 3 times per week for 8 weeks of intervention. The statistical analysis employed a paired t-test and simple linear regression test. The results of this study revealed that the skipping intervention had a significant effect on the reduction of BAZ (p<0,05; R2=0,286) and WHR (p<0,05; R2=0,174) in the skipping group compared to the control group. There was no significant difference in the muscle strength between the skipping and control groups (p>0,05; R2=0,049). In conclusion, skipping for a duration–4-8 minutes was conducted three times a week for 8 weeks, which reduced the value of BAZ and WHR in adolescent girls.